Hubungan Pengetahuan Gizi dengan Status Gizi pada Remaja Putri di SMP Negeri 5 Kendari Tahun 2024 - Wa Ode Siti Nur Asnia; Devi Savitri Effendy; Ruwiah Ruwiah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Adolescence is a period of gradual transition from childhood to adulthood. Adolescent girls as prospective mothers are vulnerable to nutritional problems. The level of nutritional knowledge is considered important in influencing the nutritional status of adolescents. This research aims to determine the relationship between nutritional knowledge and the nutritional status of adolescent girls at SMP Negeri 5 Kendari in 2024.The type of research used is descriptive research with a cross sectional design. The population in this study was all 7th and 8th grade female students at SMP Negeri 5 Kendari in the 2024 academic year, totaling 367 female students and the sample size was 79 female students using a proportionate stratified random sampling technique. From the research results, nutritional knowledge was obtained in the good category, namely 97,5% and nutritional status in the good category, namely 88,6%. The results of the bivariate analysis showed that there was no relationship between nutritional knowledge and the nutritional status of adolescent girls with a value of p = 1,00.